Assessment of oxidative stress markers and hearing thresholds in patients with obstructive sleep apnea-hypopnoea treated with cysteine and superoxide dismutase therapy. - Serra, Agostino; Maiolino, Luigi; Cocuzza, Salvatore; Di Luca, Milena; Campione, Gianluca; Licciardello, Luisa; Di Mauro, Paola (Acta Biomedica Atenei Parmensis, 2017)
Background and aim of the work: In OSAHS, the hypoxia and reoxygenation cicles, maintain a state of oxidative stress, which seems to cause a change in the oxidative balance. Our aim is to compare the markers of oxidative stress with audiological findings and OSAHS severity, in OSAHS patients untreated and also treated ones, with cysteine and superoxide dismutase. Methods: 65 patients (42 Men, 23 Women) with 30-65 years age range have been enrolled, with a mean age of 52.6 ± 13.3 years with moderate OSAHS. We have analyzed plasma and lymphocyte markers of oxidative stress (glutathione, thioredoxin and heat shock protein) and they were underwent tonal audiometry. Patients were divided in two groups: Group A (32 patients) included patients treated for 8 weeks with cysteine and superoxide dismutase; Group B (33 patients) included patients untreated. Results: The research showed a significant increase in reduced glutathione levels (p<0.05) in OSAHS patients treated; conversely, it showed a decrease of oxidized glutathione level (p<0.05) in treated patients than OSAHS untreated ones. The thioredoxin values, in untreated OSAHS patients, appear to be reduced than in OSAHS patients treated (p<0.05), and that the heat shock protein values were more elevated in untreated OSAHS patients (p<0.05). Finally, it was found that a correlation exists between the severity of OSAHS and auditory dysfunction. Conclusions: The study of the oxidative stress markers has produced results which lead to support the idea that, in a personalized therapy context, the use of antioxidant therapy can cooperate effectively the first choice treatment.